A Statistical Analysis of Social Media as a New Investigative Tool in Marketing - Anand, Nishtha; Mahajan, Renuka (International Journal of Computer Sciences and Engineering, 2014)
In this paper an analysis of the existing Social Media Marketing practices as a new investigating tool has been executed that can yield some indispensable data to keep up with the trends, competitor strategies, and developments in the market. The objective of this exercise is to expedite the process of making a novice entrepreneur into a seasoned pro with the help of social networking. The less known brands and small business have been scrutinized to devise an analysis based on the above mentioned peculiarity.